Comparative Analysis of Human, Mouse, and Pig Glial Fibrillary Acidic Protein Gene Structures. Issue 2 (2nd April 2016) - Eun, Kiyoung; Hwang, Seon-Ung; Jeon, Hye-Min; Hyun, Sang-Hwan; Kim, Hyunggee
ABSTRACT: Comparing the coding and regulatory sequences of genes in different species provides information on whether proteins translated from genes have conserved functions or gene expressions are regulated by analogical mechanisms. Herein, we compared the coding and regulatory sequences of glial fibrillary acidic protein (GFAP) from humans, mice, and pigs. The GFAP gene encodes a class III intermediate filament protein expressed specifically in astrocytes of the central nervous system. On comparing the mRNA, regulatory region (promoter), and protein sequences of GFAP gene in silico, we found that GFAP mRNA 3′-untranslated region (3′-UTR), promoter, and amino acid sequences showed higher similarities between humans and pigs than between humans and mice. In addition, the promoter-luciferase reporter gene assay revealed that the pig GFAP promoter functioned in human astrocytes. Notably, the 1.8-kb promoter fragment upstream from transcription initiation site showed strongest transcriptional activity compared to 5.2-kb DNA fragment or other regions of GFAP promoter. We also found that pig GFAP mRNA and promoter activity increased in pig fibroblasts by human IL-1β treatment. Taken together, these results suggest that the regulatory mechanisms and functions of pig genes might be more similar to those of humans than mice, indicating that pigs, particularly miniature pigs, are a useful model for studying human biological and pathological events. Abbreviations: CNS: central nerve system; GFAP: glial fibrillary acidic protein; UTR: untranslated region; IL-1β: interleukin-1β; BLAST: basic local alignment search tool; CDS: coding sequence